2015
DOI: 10.25011/cim.v38i4.24260
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Lowers Systemic Inflammatory Response in Coronary Artery Bypass Graft Accompanied by Cardiopulmonary Bypass Surgery: A Randomized Controlled Study

Abstract: Purpose: Cardiopulmonary bypass (CPB) is commonly associated with a systemic inflammatory response that may lead to severe complications. Classic signs of systemic inflammatory response syndrome are complement activation and changes in cytokine and acute phase reactant levels. The effects of rosuvastatin after CPB on interleukin-6 (IL-6), interleukin-10 (IL-10), interleukin-18 (IL-18) and High Sensitivity C-Reactive Protein (hs-CRP) levels were investigated.Methods: Thirty-seven male and thirteen female patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Preoperative statin therapy was associated with a reduction in post-CPB inflammation [95, 96] and an improvement in morbidity and mortality after cardiac surgery [9799]. However, a recent meta-analysis of randomized control trials (RCTs) found no evidence of benefit for patients’ outcomes [100].…”
Section: Clinical Implications Of Ecls-associated Inflammatory Responsementioning
confidence: 99%
“…Preoperative statin therapy was associated with a reduction in post-CPB inflammation [95, 96] and an improvement in morbidity and mortality after cardiac surgery [9799]. However, a recent meta-analysis of randomized control trials (RCTs) found no evidence of benefit for patients’ outcomes [100].…”
Section: Clinical Implications Of Ecls-associated Inflammatory Responsementioning
confidence: 99%
“…The qualitative and quantitative changes in alveolar surfactant of patients with ARDS have been proven [7][8][9]. Similarly, due to endothelial cells damage, all post-cardiac surgery infants who had ARDS suffered surfactant dysfunction, destruction and inactivation [10][11][12]. Yet, limited study [13] showed preliminary therapeutic effect of surfactant therapy on these patients, especially, the association between age or drug dose and the e cacy of surfactant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative and quantitative changes in alveolar surfactant of patients with ARDS have been proven [6][7][8]. Similarly, due to endothelial cells damage, all post-cardiac surgery infants who had ARDS suffered surfactant dysfunction, destruction and inactivation [9][10][11]. Yet, limited study [12] showed preliminary therapeutic effect of surfactant therapy on these patients, especially, the association between age or drug dose and the efficacy of surfactant therapy.…”
Section: Introductionmentioning
confidence: 99%